Visual theater as performative theater - Cintra, Wagner [UNESP] (Univ Estado Santa Catarina-udesc, 2018)
One of the phenomena that have become apparent in the world of theater at the beginning of the 20th century was its approach to the visual arts. Such phenomenon still reverberates nowadays by innumerous artistic manifestations that are constantly seeking for the development of innovative ways of making art. Visual Theater, in turn, emerges as a new theatrical language, which is marked by the existing hybridity in the interface between theater and visual arts, and therefore, brings to the stage a series of elements that are conjured up at the same poetical level among both types of arts: puppets, objects, actors and actresses etc. In that way, this kind of work intends to give voice to a theatrical language whose concepts are under development and that are still an unknown territory, especially in Brazil. This article presents a general view about this universe emphasizing the human presence in scene.
Keywords: Visual Theater; visual Arts; hybridity